Using Digital Personal Data and Its Ethical Contradictions - Irina ASEEVA (Communications of International Proceedings, 2021)
Information and communication technologies are deeper and deeper getting into all the spheres of human life, changing the forms of everyday communication, intruding into personal sphere, violating the right for confidentiality. Modern computers, smartphones video cameras, the Internet and social networks undoubtedly broaden communication platforms. However, at the same time new technologies actualize the need of “digital culture”, one of the basics of which is the right for personal privacy. In this article we justify the ethical arguments in defense of privacy in “digital epoch” through understanding the contradictions that arise.
Keywords: Digitalization; Digital Culture; Personal Data; Ethical Arguments in Defense of Privacy